2010
DOI: 10.1115/1.4000763
|View full text |Cite
|
Sign up to set email alerts
|

Forced Response Analysis of Integrally Bladed Disks With Friction Ring Dampers

Abstract: This paper investigates a damping strategy for integrally bladed disks (blisks) based on the use of friction rings. The steady-state forced response of the blisk with friction rings is derived using the so-called Dynamic Lagrangian Frequency-Time method adapted to cyclic structures with rotating excitations. In addition, an original approach for optimal determination of the number of Fourier harmonics is proposed. In numerical applications, a representative compressor blisk featuring several rings is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 21 publications
0
32
0
2
Order By: Relevance
“…However, for blisks in which blade-root joints no longer exists, traditional technologies cannot be used straightforward. A technological answer to this issue was recently proposed in [8]; it consists in using friction rings held in contact underside the wheel of the blisk due to centrifugal load. The friction ring dampers can be located anywhere underside the "rim" of the blisk.…”
Section: Introductionmentioning
confidence: 99%
“…However, for blisks in which blade-root joints no longer exists, traditional technologies cannot be used straightforward. A technological answer to this issue was recently proposed in [8]; it consists in using friction rings held in contact underside the wheel of the blisk due to centrifugal load. The friction ring dampers can be located anywhere underside the "rim" of the blisk.…”
Section: Introductionmentioning
confidence: 99%
“…Most research is currently focused on analyzing the forced response of the structure with an additional ring damper. Laxalde et al [3,4] used a dynamic time-frequency conversion method to analyze the forced response of a bladed disk structure with a ring damper; they found that the effect of the ring damper depends on friction energy dissipation on the contact surface between the ring damper and the structure. Zucca et al [5,6] characterized the frictional force of the contact surface as a function of the tangent and normal stiffness as depending on the amplitude, and calculated the periodic response of the system in the frequency domain via the harmonic balance method.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additional damping treatment was essential to conduct vibration reduction of the mistuned blisk. So far, various dry friction dampers have been used in the bladed disk assemblies because of their simplicity in implementation and superiority in performance, such as the shroud friction dampers [7,8], the under-platform dampers [9,10] and the friction ring dampers [11,12]. However, these traditional dampers were very difficult to apply to the blisk due to its special one-piece structure.…”
Section: Introductionmentioning
confidence: 99%